The value of q(x) is ![2 x+5](https://tex.z-dn.net/?f=2%20x%2B5)
The value of r(x) is ![6](https://tex.z-dn.net/?f=6)
Explanation:
The given expression is ![\frac{2 x^{2}+13 x+26}{x+4}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20x%5E%7B2%7D%2B13%20x%2B26%7D%7Bx%2B4%7D)
We need to rewrite the expression in the form of ![q(x)+\frac{r(x)}{b(x)}](https://tex.z-dn.net/?f=q%28x%29%2B%5Cfrac%7Br%28x%29%7D%7Bb%28x%29%7D)
Simplifying the expression, we get,
![\frac{2 x^{2}+8 x+5x+26}{x+4}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20x%5E%7B2%7D%2B8%20x%2B5x%2B26%7D%7Bx%2B4%7D)
Separating the fractions, we have,
![\frac{2 x^{2}+8 x}{x+4}+\frac{5 x+26}{x+4}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20x%5E%7B2%7D%2B8%20x%7D%7Bx%2B4%7D%2B%5Cfrac%7B5%20x%2B26%7D%7Bx%2B4%7D)
-----------(1)
Now, we shall further simplify the term
, we get,
![\frac{5 x+26}{x+4}=\frac{5 x+20}{x+4}+\frac{6}{x+4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%20x%2B26%7D%7Bx%2B4%7D%3D%5Cfrac%7B5%20x%2B20%7D%7Bx%2B4%7D%2B%5Cfrac%7B6%7D%7Bx%2B4%7D)
Common out 5 from the numerator, we have,
![\frac{5 x+26}{x+4}=5+\frac{6}{x+4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%20x%2B26%7D%7Bx%2B4%7D%3D5%2B%5Cfrac%7B6%7D%7Bx%2B4%7D)
Substituting the value
in the equation(1), we get,
![2 x+5+\frac{6}{x+1}](https://tex.z-dn.net/?f=2%20x%2B5%2B%5Cfrac%7B6%7D%7Bx%2B1%7D)
Thus, the expression
is in the form of ![q(x)+\frac{r(x)}{b(x)}](https://tex.z-dn.net/?f=q%28x%29%2B%5Cfrac%7Br%28x%29%7D%7Bb%28x%29%7D)
Hence, we have,
![q(x)=2 x+5](https://tex.z-dn.net/?f=q%28x%29%3D2%20x%2B5)
and
![b(x)=x+4](https://tex.z-dn.net/?f=b%28x%29%3Dx%2B4)